(untitled) - Trigeorgis, Lenos (Cambridge, Massachusetts, 1996)
The book brings together a wealth of previously scattered knowledge and research on the new flexibility in corporate resource allocation and in the evaluation of investment alternatives. In comparison to static cash-flow approaches, the more dynamic paradigm of real options incorporates decisions on whether to defer, expand, contract, abandon, switch use, or otherwise alter a capital investment. It reviews current techniques of capital budgeting and details an approach that provides a means of quantifying the elusive elements of managerial flexibility in the face of unexpected changes in the market. Also discussed are the strategic value of new technology, the interdependence of projects, and competitive interaction
Keywords: Capital budget,Resource allocation